The effects of the home-based exercise during COVID-19 school closure on the physical fitness of preschool children in China - Liang, Zhenwen; Deng, Cheng; Li, Dan; Lo, Wai Leung Ambrose; Yu, Qiuhua; Chen, Zhuoming (Frontiers in Pediatrics, 2022)
Abstract Background: Social distancing and school closures during COVID-19 pandemic reduced the physical activities of the preschool children living in China. However, the effects of home-based exercise on physical fitness of Chinese preschool children during COVID-19 school closures is still unknown. This study aimed to investigate the effects of home-based exercise on physical fitness of Chinese preschool children during COVID-19 school closure. Methods: In this retrospective analysis, data from 1608 Chinese preschool children (aged 3-5.5 years) in a second-tier city of Guangdong Province of China (Zhongshan city) were extracted from 3 successive National Physical Fitness Measurement (NPFM) from 2019 to 2021. NPFM consists of weight, height and 6 subtests of physical fitness including 10-m shuttle run test (SRT), standing long jump (SLJ), balance beam walking (BBW), sit-and-reach (SR), tennis throwing (TT), and double-leg timed hop (DTH) tests. The change differences or change ratios of all the items in NPFM between any two successive years from 2019 to 2021 were compared. The exercise profiles about home-based and outdoor exercise before, during and after COVID-19 school closure were obtained from 185 preschool children via retrospective telephone survey. Results: Between 2019 and 2021, 1608 preschool children were included in this study. We observed larger change ratios in SLJ, SR, TT, and DTH tests during school closure than after school closure. But the children showed lower reduction rates in the completion time of SRT and BBW. During school closure, higher change ratios in SLJ and TT were observed in the children primarily participating home-based exercise than those primarily participating outdoor exercise. However, no statistical difference were observed in the changes of SRT and BBW between home-based and outdoor training groups. Conclusion: The home-based exercise program might be an alternative approach to improve the physical fitness of preschool children during COVID-19 school closure, but could not be beneficial to speed-agility and balance functions. A specific guideline geared towards home-based exercise program during COVID-19 outbreak is highly needed.